Étrange ou ennemi ? Typologie de l’étranger, construction identitaire et circonvolutions du discours dans l’Angleterre des XVIe et XVIIe siècles - Michèle Vignaux (Revue LISA)
Taking Bacon’s and Coke’s definitions of strangers in the Case of the Post-Nati (1605) as a starting point, this article examines the implications of defining English citizens as subjects owing allegiance to the King of England by looking at the various types of allegiance (which may be implicit or explicit, geographically or temporally limited or unlimited). It concludes that the one unbridgeable chasm was with perpetual enemies, that is with infidels, rather than with strangers as such. Ironically, the monstrosities of Mandevillian lore resurfaced with the discovery of the “fourth continent” when in the face of economic “necessity” Christian discourse was trapped into labelling as monstrous, and denying humanity to, those strangers who were to be used as slaves.